Addition of histone deacetylase inhibitors does not improve prognosis in patients with myelodysplastic syndrome and acute myeloid leukemia compared with hypomethylating agents alone: A systematic review and meta-analysis of seven prospective cohort studies. (August 2018) - Pan, Tingting; Qi, Jiaqian; You, Tao; Yang, Liping; Wu, Depei; Han, Yue; Zhu, Li
Highlights: This is the first meta-analysis for evaluating histone deacetylase inhibitors. Addition of histone deacetylase inhibitors hardly improve myeloid malignancies. We put forward that epigenetics information should be embraced in further studies. Abstract: Aim: To compare the efficacy and safety between hypomethylating agent (HMA) alone and the combination of HMA and histone deacetylase inhibitor (HDACi) in myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). Methods: We performed a systematic review and meta-analysis of all available cohort studies regarding the comparison of HMA alone and in combination with HDACi for MDS and AML. Embase and Pubmed databases were searched for relevant studies. The overall hazard ratios for the HMA alone and HDACi combination were extracted. Heterogeneity among the included studies was evaluated by Cochrane's Q Test and I 2 statistics. A random-effect model or a fixed-effect model was applied depending on the heterogeneity. Subgroup analysis was used to evaluate the source of heterogeneity. Results: Seven studies comprising 922 patients (458 patients treated with HMA alone and 464 with HMA and HDACi) were included in the analysis. Pooled data showed no significant differences in complete remission (CR) rates, hematologic improvement (HI), overall response rate (ORR), overall survival (OS), and toxicities between HMA alone treatment and HMA with HDACi regimens. Conclusions: HDACi and HMA combination does not appear to be more effective and better tolerated than HMA alone. Future randomized controlled trials are needed to confirm its efficacy and safety.